Forced Sterilization as Antigypsyism: The Czechoslovak / Czech and Slovak Examples - Albert, Gwendolyn (Romano džaniben, 2019)
The subject of the sterilization of women without their free and informed choice and consent, Romani women in particular, is argued by the author to be a prime example of the impact of antigypsyism on the practice of medicine and social work in the former Czechoslovakia and its successor states. This paper summarizes civil society efforts to convince authorities in the former Czechoslovakia and its successor states, the Czech Republic and Slovakia, that these acts constitute human rights violations and should therefore be redressed. The responses to these civil society effortsby these authorities and by international human rights bodies will be reviewed. The author has been attempting, since 2004, to aid the Romani women in their communications with the Czech authorities about achieving compensation, justice, and redress for the aforementioned abuses.
Keywords: forced sterilization; reproductive rights; obstetric violence; Romani women; Czechoslovakia; Czech Republic; Slovak Republic